Effectiveness of Project-Based Learning in Accounting Practicum: A Quasi-Experimental Study - Rachmah, Siti; Nur Maula, Farisa (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the effectiveness of implementing Project-Based Learning (PBL) in improving student learning outcomes and perceptions in the Accounting Practicum course. The primary background of this research is the gap between theory and practice, as well as the industry demand for graduates capable of solving real-world problems. The research method employed was a quasi-experimental design with pre-test and post-test measures involving 62 students. The PBL implementation was conducted in two stages: the structured conceptual briefing stage (pre-test) and the design stage of an accounting module project based on actual micro, small, and medium enterprises (post-test). The results indicate a statistically significant improvement in learning outcomes (p < 0.001), with the mean score increasing from 77.06 to 81.46. Qualitative analysis of student project reports demonstrated enhanced abilities in problem identification, system design, and solving complex problems. The findings conclude that PBL is effective in enhancing students' cognitive competencies and practical skills, as well as transforming their roles from passive recipients to active and creative solution designers.